Effects of instructional scaffolding on the reading ability of ESL students / Josephine Maung - Maung, Josephine @ Faridah (2009)
The study aimed to investigate the effects of instructional scaffolding on the students’ reading ability. The study involved a group of Sixth Form students at SM Sunny Hill Sarawak. A quasi-experimental research design was employed which engaged an experimental group (32 students) and a control group (29 students). The experimental group went through reading sessions via instructional scaffolding for a period of 30 hours, where the students were provided with support and guidance to comprehend reading texts. The teacher’s implementation of instructional scaffolding was observed by two observers using a self-constructed structured observation scheme. The students’ perception of the usefulness of instructional scaffolding was determined using a 25-item likert-type questionnaire. Semi-structured interviews were also conducted on the teacher in the experimental group to determine the extent to which instructional scaffolding was a useful tool. The quantitative data collected was analysed using SPSS 16.0 for descriptive statistics whereas the qualitative interview data was analysed inductively and deductively before any final conclusions were made. The two groups were also given a pre-test and a post-test to investigate their reading comprehension performance. The test scores were analysed using Pearson correlation test for significant difference. The non-parametric Pearson test results on the pre and post tests indicated that there was a significant increase in mean scores of both the experimental and control groups. The fact that the experimental group indicated significant improvement in their pre-test-post- test performance seems to suggest that instructional scaffolding is an effective teaching approach to help enhance students’ reading ability.